2021
DOI: 10.3390/su13158518
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Adaptation and Sectoral Policy Coherence in the Caribbean

Abstract: Climate change is an existential threat to small island developing states. Policy coherence aims to create synergies and avoid conflicts between policies. Mainstreaming adaptation across multiple sectors and achieving greater coherence amongst policies is needed. The paper applies qualitative document analysis, content analysis, and expert interviews to examine the degree of coherence between climate-sensitive sector policies in framing climate change adaptation and the adaptation goals outlined in the nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…These perspectives examine coherence by assessing the alignment of local to national, and even national to international policies. In accordance with this perspective, Lewis and Su (2021) studied the degree of coherence between climate-sensitive sectors and showed that "policies must align to combat climate change" (p. 17).…”
Section: Theoretical Perspectives Of Policy Coherence Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…These perspectives examine coherence by assessing the alignment of local to national, and even national to international policies. In accordance with this perspective, Lewis and Su (2021) studied the degree of coherence between climate-sensitive sectors and showed that "policies must align to combat climate change" (p. 17).…”
Section: Theoretical Perspectives Of Policy Coherence Studiesmentioning
confidence: 99%
“…From another perspective and using the scoring framework ofNilsson et al (2012),Muscat et al (2021) used an online survey to assess the interaction between agro-food and bioeconomy policies in the European Union. Their ratings from an experts' survey (n = 24) allowed them to determine the level of coherence between policies in these two areas within the European Union.3.3.4 | Focus groups, interviews, and workshopsSeveral authors (e.g.,Antwi-Agyei et al, 2017;Huttunen, 2015;Lewis &Su, 2021 andMoure et al, 2021) used focus groups (n = 7) and workshops (n = 8). For example, from a bottom-up perspective of analyzing PC in ethanol production in Thailand,Chaya et al (2019) used focus groups to gather small-scale farmers' perceptions about the role of technologies in their operations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Since some incumbent actors (e.g., the electricity sector) have an influential hold on the development of sustainable energy sectors, it is crucial to have a deeper understanding of different stakeholders' perceptions of the electricity sector as a leader in environmental performance and its implications for energy policymaking, environmental sustainability, and the implementation and achievement of a holistic sustainable development strategy. Additionally, studies on energy and innovation highlight the centrality and coherence of policy design for steering policy outcomes [20,[36][37][38]. For example, industrial policy measures can enable the accumulation of firm-level capabilities that are critical for developing economies seeking to escape the middle-income trap [39].…”
Section: Conflicts Of Interest Between Stakeholders Energy Policymaki...mentioning
confidence: 99%